Seven new species of the genus Deltoplastis Meyrick, 1925 (Lepidoptera: Lecithoceridae) - Yu, Shuai; Park, Kyu-Tek; Wang, Shuxia (Zootaxa, 2019)
Seven new species of the genus Deltoplastis Meyrick are described: D. acutangulata Wang et Yu, sp. nov., D. anatoliana Wang et Park, sp. nov., D. multidentalis Wang et Yu, sp. nov. and D. similihoristis Wang et Yu, sp. nov. from China; D. aculeata Wang et Yu, sp. nov. and D. spatuliunca Wang et Yu, sp. nov. from Malaysian Borneo; and D. ovidiscalis Park et Wang, sp. nov. from Vietnam. Deltoplastis horistis (Meyrick, 1910) is newly recorded in China and its female is described for the first time. Images of adults and genitalia of the new species are provided.